Science and Theology for Everyone: How Climate Science is Shaping Christianity in the UK. Issue 2 (1st April 2021) - Gordon, Caleb; Malcolm, Hannah
Abstract : This article analyses the growing participation of UK Christians in climate initiatives over the last five years. In many cases, climate science is cited as a necessary consideration for the fulfilment of already-existing Christian commitments. This represents a significant shift in the ways UK Christians understand the role of dialogue between theology and the sciences; previous science and theology dialogue has usually been treated as an area of expert concern, primarily offering insight into apologetics or specific ethical problems. By contrast, the dialogue between climate science and theology has seen the emergence of non-technical leadership amid the expectation that climate science plays a critical role in re-examining the meaning of Christian life, both for individuals and as communities.